Precision Jigs and Molds: Innovative Design and Application - Peng Zheng (Innovation in Science and Technology, 2025)
Precision jigs and molds are key tools in modern manufacturing, playing a vital role in enhancing product quality, boosting production efficiency, and reducing costs. They ensure product consistency and repeatability, minimize errors, and improve quality. Optimized design and processes can shorten production cycles and enhance efficiency. Moreover, by reducing scrap rates and extending service life, they significantly cut production costs. This thesis explores innovative design methods for precision jigs and molds, including topology optimization, biomimetic design, intelligent design, and multidisciplinary integration design. These methods have achieved remarkable results in practical applications. By optimizing structure, improving material properties, and incorporating intelligent design, the performance and service life of molds and jigs have been significantly enhanced.